AN INTEGRATED APPROACH TO EOR PROJECT DECISION MAKING STUDY USING PERTAEOR-LITE SOFTWARE: FROM SCREENING TO DECISION ANALYSIS - Daniati, Arik
Conducting a comprehensive evaluation to provide an alternative Enhanced Oil Recovery (EOR) project that is feasible to implement in a field poses a challenge during the early stages. This study aims to implement an integrated EOR project decision analysis workflow using Pertamina’s internal software PertaEOR-lite© in the "ADP" field with different sensitivity scenarios for pattern area and number of infill wells. The predictive model developed by the US DOE was used to predict reservoir performance based on the most suitable EOR method. Economic evaluation is carried out to determine NPV, IRR, and POT values, as well as the sensitivity of variables that affect the economy. Risk analysis is carried out using Monte Carlo simulation. The optimal scenario is determined using the stochastic optimization method. Analysis The decision was made using deterministic analysis and probabilistic analysis to obtain the Expected Monetary Value of each scenario. Based on the EOR screening, the predictive models developed were miscellar polymer flooding and polymer flooding. Six field development scenarios have been determined, and the study shows that the adjustment of pattern area and considerations is necessary to infill wells to generate high economic benefits from increased production of CEOR. The best development scenario is the MP 20 scenario, which is a five-spot pattern scenario with a pattern area of 20 acres and the addition of 8 production wells infill, 42 injection wells, and 8 conversion wells from production wells to injection wells. The risk value of this scenario is 12.95%, with an EMV value of 45,085.40 K.D. Economically, the NPV, IRR, and POT are 54,895.54 K.USD, 29.23%, and 2.22 years, respectively.